The effect of an Er,Cr:YSGG laser on external adaptation of healthy and decayed cavities - Kabbach, William [UNESP]; Tonetto, Mateus Rodrigues [UNESP]; Frizzera, Fausto [UNESP]; Zezell, Denise Maria; Bandeca, Matheus Coelho; Campos, Edson Alves [UNESP]; Borges, Alvaro Henrique; Andrade, Marcelo Ferrarezi [UNESP] (Iop Publishing Ltd, 2014)
The aim of this study was to evaluate the influence of chlorhexidine and Er, Cr:YSGG laser irradiation on the bond strength and external adaptation in mixed healthy and caries-affected class V cavities before and after thermal cycling. Thirty-six cavity preparations were made in mixed class V buccal human molars, half of them being artificially caries-induced. Any remaining affected dentin was removed from the cavity with a round burr at low speed. The teeth were divided into six groups, according to cleaning agent for both healthy and caries-induced dentin: no treatment, chlorhexidine and erbium, chromium-doped: yttrium, scandium, gallium, garnet (Er,Cr:YSGG) laser irradiation. A Filtek P90 (3M ESPE, St Paul, MN, USA) silorane adhesive restorative system was used. The specimens were subjected to 5000 thermal cycles (5-55 degrees C 60 min). Epoxy replicas were obtained to characterize the external adaptation under scanning electron microscopy. The average percentages of non-continuous margins were 5.41% and 6.49% in enamel dentin before thermal cycling and 25% and 33.7% after thermal cycling, respectively. The caries-affected and laser irradiated cavities showed higher non-continuous margins. Thermal cycling was able to raise the percentage of non-continuous margin for all groups. Chlorhexidine did not affect the marginal adaptation results, and the Er,Cr:YSGG laser irradiation showed significantly worse results compared with the control group.
Keywords: composite resins; chlorhexidine; laser; dental caries; SEM